The Role of Civil Servant Professionalism and The Merit System on Employee Sustainable Performance Through Value Co-Creation - Syahraini, Mira; Nasir Hamzah, Muhammad; Rahim, Abdul Rahman; Sultan, Zulkifli (Jurnal Manajemen Bisnis, 2025)
Research aims: This study aims to promote employee sustainable performance in the local government sector to support the achievement of organizational sustainability goals by examining the role of three important variables, namely civil servant professionalism, merit system, and value co-creation.Design/Methodology/Approach: The research was conducted on civil servants in the Bukittinggi City Local Government with a total of 230 respondents. The research used a quantitative approach with a survey method and analyzed the data using structural equation modeling PLS.Research findings: The results show that civil servant professionalism and value co-creation each had a significant positive effect on employee sustainable performance. Meanwhile, merit system had no effect on employee sustainable performance. Moreover, civil servant professionalism and merit systems each had a significant positive effect on value co-creation. Civil servant professionalism and merit system each had a significant positive effect on employee sustainable performance through value co-creation. This study demonstrates that value co-creation serves as a mediator, enhancing the impact of civil servant professionalism and merit system on employee sustainable performance.Theoretical Contribution/Originality: These traits show how HRM practices play a strategic role in attaining long-term corporate success.Practitioners/Policy Implications: The findings provide strategic recommendations for local government agencies to enhance civil servant professionalism and the merit system, initiating discourse on the efficacy of the merit system in local government, while also optimizing value co-creation as a collaborative method to improve employee sustainable performance. Consequently, this will ultimately facilitate the attainment of sustainable organizational success.Research Limitations/Implications: This research has limitations, specifically that it was conducted just on a single local government entity.